Analyzing the Effect of @Kulinerkoko’s Tiktok Food Content on the Foodie Behavior of University Students in Medan - Hafizhah, Syafira Noer; Rozi, Fakhrur (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2025)
This study aims to examine the extent to which TikTok content from the food vlogger @KulinerKoko influences foodie behavior among university students in Medan. The increasing trend of food vlogging on social media has made food vloggers the primary reference for culinary recommendations, which impacts the preferences and consumption habits of the younger generation, especially university students. The research was conducted using a quantitative approach through a survey of 96 respondents, selected using Lemeshow’s formula. The instrument used underwent validity and reliability testing, indicating that all items were appropriate and consistent (r-count r-table; Cronbach’s Alpha 0.8). Data analysis was carried out using normality, linearity tests, and simple linear regression with the help of SPSS version 20. The findings show a positive and significant influence of @KulinerKoko’s content on the foodie behavior of students, as indicated by a significance value of 0.000 ( 0.05) and a regression coefficient of 0.583. The R Square value of 0.249 indicates that 24.9% of the variation in foodie behavior can be explained by the displayed content, while the remaining variation is influenced by other factors. The content, including food reviews, attractive visuals, and communicative delivery, has proven to encourage students to try new foods, visit recommended places, and share their experiences on social media.